Invited review: Architectures and mechanisms of ATP binding cassette proteins. Issue 8 (20th May 2016) - Hopfner, Karl‐Peter
ABSTRACT: ATP binding cassette (ABC) ATPases form chemo‐mechanical engines and switches that function in a broad range of biological processes. Most prominently, a very large family of integral membrane NTPases—ABC transporters—catalyzes the import or export of a diverse molecules across membranes. ABC proteins are also important components of the chromosome segregation, recombination, and DNA repair machineries and regulate or catalyze critical steps of ribosomal protein synthesis. Recent structural and mechanistic studies draw interesting architectural and mechanistic parallels between diverse ABC proteins. Here, I review this state of our understanding how NTP‐dependent conformational changes of ABC proteins drive diverse biological processes. © 2016 Wiley Periodicals, Inc. Biopolymers 105: 492–504, 2016.